Sex differences in classical and skating cross-country skiing time-trial competitions - Talsnes, R. K.; Kocbach, J.; Sandbakk, Ø.; Losnegard, T. (Sport Sciences for Health, 2025)
Purpose To compare differences in speed, sub-technique selection, and kinematics between male and female cross-country skiers during 10-km time-trial competitions.